Leadership, Social Capital and Village Finance: Development Capital For Village Sustainability - Shaleh , Khairul; Fitri Sukmawati; Silviana (Faculty of Economics and Business, Universitas Warmadewa, 2024)
This research aims to capture the combination of leadership, social capital, and village finance in realizing rural sustainable development. Field research seeks to understand social reality by the actual circumstances that exist and occur in a particular area. Researchers obtain scans of social reality through a qualitative research approach. Researchers in this context use qualitative research with an emphasis on case studies. The research used participant observation techniques, in-depth interviews, and field documentation. The results show that the village's financial capacity is an essential element. However, more importantly, the legitimacy and trust of the community in the leadership of the village head can establish communication in campaigning for village environmental conservation with a sustainable development orientation. The village head presents himself as a protector through humanist communication interactions with all elements in the village environment. The legitimacy of power and trust in the formal village leader leads to the belief of the community to take part in village development.